Evaluating the safety and tolerability of inpatient sacubitril/valsartan initiation in a community hospital - Katie L. Peppin; Katie B. Tellor; Anastasia L. Armbruster; Martin W. Schwarze (Greater Baltimore Medical Center, 2020)
Background Sacubitril/valsartan has been incorporated into guidelines based on the results of the PARADIGM-HF trial, which demonstrated reduced mortality in stable patients with heart failure with reduced ejection fraction (HFrEF). Sacubitril/valsartan is recommended in addition to other HF therapies in place of an angiotensin-converting-enzyme inhibitor or angiotensin-receptor-blocker. Objectives To evaluate the safety and tolerability of sacubitril/valsartan initiation in a community hospital. Design/methods This single-center, retrospective review evaluated patients that received ≥24 hours of sacubitril/valsartan therapy August 2015-March 2018. The primary outcome included the incidence of hypotensive events during hospitalization. Secondary outcomes included: incidence of inpatient acute kidney injury (AKI) and hyperkalemia, rates of inpatient discontinuation, and change in ejection fraction (EF) ≥30 days after initiation. Results Of the 59 patients included, 21 (35.6%) experienced a hypotensive event. A total of 6 patients (10.2%) discontinued therapy while inpatient, which was more likely in patients that developed AKI (n = 3; p = 0.005) or those who experienced a hypotensive event (n = 5; p = 0.018). There was a significant difference in mean EF from baseline to ≥ 30 days post-initiation (24.8% vs. 33.2%; p = 0.018). Conclusion Careful patient selection and monitoring for hypotension, AKI, and hyperkalemia can help increase successful outcomes and improve patient safety.